Diversity in the film industry: A social network analysis of #cannes2022 on Twitter - Rizky Wulan Ramadhani; Edy Prihantoro; Sabrina Rahma Utami; Trini Saptariani; Anacostia Kowanda (Universitas Padjadjaran, 2023)
Background: The 2022 Cannes Film Festival was held from May 17 – 28, 2022, in Cannes, France. The 2022 Cannes Film Festival succeeded in attracting public attention, shown through tweets using #Cannes2022 uploaded in various languages, which show diversity. Purpose: This study aims to determine the distribution of the #Cannes2022 data at the actor level and the diversity of languages used in the #Cannes2022. Methods: The method of this research is a mixed method by combining quantitative and qualitative methods. Quantitative methods were used to obtain 2,500 tweets using the Netlytic application. Qualitative methods were used to analyze the language used in those tweets. Results: The results of this study indicate that @festival_cannes, @21metgala, @iuteamstarcandy, and @filmupdates are famous and important actors because they always provide updates related to Cannes 2022. Those actors initiate the #Cannes2022 communication network and become reference material. In the #Cannes2022 communication network, there are 24 languages used, including English, Thai, Japanese, French, and Spanish. English is dominant, with a percentage of 51.96%, followed by French, with a percentage of 31.48%. English and French are dominant because popular actors use them in disseminating information about Cannes 2022. Other languages are not dominant because actors with few followers only upload them. The language used in the #Cannes2022 communication network is already quite diverse but still dominated by English. Implications: Popular actors should use other languages to increase diversity at the Cannes Film Festival.